Accuracy and Prognostic Significance of Oncologists' Estimates and Scenarios for Survival Time in Advanced Gastric Cancer. (1st April 2019) - Vasista, Anuradha; Stockler, Martin; Martin, Andrew; Pavlakis, Nick; Sjoquist, Katrin; Goldstein, David; Gill, Sanjeev; Jain, Vikram; Liu, Geoffrey; Kannourakis, George; Kim, Yeul Hong; Nott, Louise; et al.
Abstract: Background: Worst‐case, typical, and best‐case scenarios for survival, based on simple multiples of an individual's expected survival time (EST), estimated by their oncologist, are a useful way of formulating and explaining prognosis. We aimed to determine the accuracy and prognostic significance of oncologists' estimates of EST, and the accuracy of the resulting scenarios for survival time, in advanced gastric cancer. Materials and Methods: Sixty‐six oncologists estimated the EST at baseline for each of the 152 participants they enrolled in the INTEGRATE trial. We hypothesized that oncologists' estimates of EST would be unbiased (∼50% would be longer or shorter than the observed survival time [OST]); imprecise (<33% within 0.67–1.33 times the OST); independently predictive of overall survival (OS); and accurate at deriving scenarios for survival time with approximately 10% of patients dying within a quarter of their EST (worst‐case scenario), 50% living within half to double their EST (typical scenario), and 10% living three or more times their EST (best‐case scenario). Results: Oncologists' estimates of EST were unbiased (45% were shorter than the OST, 55% were longer); imprecise (29% were within 0.67–1.33 times observed); moderately discriminative (Harrell's C‐statistic 0.62, p = .001); and an independently significant predictor of OS (hazard ratio, 0.89; 95% confidence interval, 0.83–0.95; p = .001) in a Cox model including performance status, number of metastatic sites, neutrophil‐to‐lymphocyte ratio ≥3, treatment group, age, and health‐related quality of life (EORTC‐QLQC30 physical function score). Scenarios for survival time derived from oncologists' estimates were remarkably accurate: 9% of patients died within a quarter of their EST, 57% lived within half to double their EST, and 12% lived three times their EST or longer. Conclusion: Oncologists' estimates of EST were unbiased, imprecise, moderately discriminative, and independently significant predictors of OS. Simple multiples of the EST accurately estimated worst‐case, typical, and best‐case scenarios for survival time in advanced gastric cancer. Implications for Practice: Results of this study demonstrate that oncologists' estimates of expected survival time for their patients with advanced gastric cancer were unbiased, imprecise, moderately discriminative, and independently significant predictors of overall survival. Simple multiples of the expected survival time accurately estimated worst‐case, typical, and best‐case scenarios for survival time in advanced gastric cancer. Abstract : Median overall survival for patients starting first‐line chemotherapy for metastatic gastric cancer is less than 1 year. This study is a follow‐up to a study that determined that most cancer patients preferred to receive survival estimates for worst‐case, typical, and best‐case scenarios rather than a single‐point estimate of median survival. This article describes the applicability of these findings in a population with advanced gastric cancer.